2022
DOI: 10.3389/fphar.2022.832732
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Peroxisome Proliferator-Activated Receptors in Kidney Diseases

Abstract: Peroxisome proliferator-activated receptors (PPARs) are members of the nuclear hormone receptor superfamily of ligand-activated transcription factors. Accumulating evidence suggests that PPARs may play an important role in the pathogenesis of kidney disease. All three members of the PPAR subfamily, PPARα, PPARβ/δ, and PPARγ, have been implicated in many renal pathophysiological conditions, including acute kidney injury, diabetic nephropathy, and chronic kidney disease, among others. Emerging data suggest that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 117 publications
0
18
0
1
Order By: Relevance
“…Activated PPAR α signi cantly reduced triglyceride levels, and moderately reduced total cholesterol levels and low-density lipoprotein cholesterol levels, thus increasing high-density lipoprotein cholesterol levels [20]. PPAR α is expressed in kidney podocytes, and activated PPAR α is able to reduce albuminuria and improve insulin resistance [21]. Activation of PPAR α may be a favorable factor for DN progression.…”
Section: Discussionmentioning
confidence: 99%
“…Activated PPAR α signi cantly reduced triglyceride levels, and moderately reduced total cholesterol levels and low-density lipoprotein cholesterol levels, thus increasing high-density lipoprotein cholesterol levels [20]. PPAR α is expressed in kidney podocytes, and activated PPAR α is able to reduce albuminuria and improve insulin resistance [21]. Activation of PPAR α may be a favorable factor for DN progression.…”
Section: Discussionmentioning
confidence: 99%
“…As a nuclear receptor transcriptional factor, PPARβ/δ is involved in many physiological and pathological processes [ 1 , 2 , 3 ]. Increasing evidence has suggested that PPARβ/δ plays an important role in the regulation of inflammatory responses [ 10 , 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…PPARβ/δ is a ligand-activated transcription factor that belongs to the nuclear hormone receptor family [ 1 , 2 , 3 ]. PPARβ/δ is ubiquitously expressed in almost all examined tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment of T2DM requires alleviation of insulin resistance and correction of dyslipidemia while preserving pancreatic β-cell function [ 4 ]. Peroxisome proliferator-activated receptor γ (PPARγ) is a ligand-activated nuclear receptor, the activation of which can heighten the sensitivity of peripheral tissues to insulin and therefore increase glucose uptake and utilization in muscle, promote adipocyte remodeling, fatty acid decomposition, and synthesis in adipose tissue while inhibiting gluconeogenesis in liver [ 6 , 7 ]. Thiazolidinediones (TZDs), PPARγ agonists, are crucial to modulating glucose and lipid metabolic homeostasis [ 8 , 9 ] and mainly act by increasing insulin sensitivity [ 10 ].…”
Section: Introductionmentioning
confidence: 99%